2023
DOI: 10.1136/bmj-2022-072909
|View full text |Cite
|
Sign up to set email alerts
|

Association of omega 3 polyunsaturated fatty acids with incident chronic kidney disease: pooled analysis of 19 cohorts

Abstract: Objective To assess the prospective associations of circulating levels of omega 3 polyunsaturated fatty acid (n-3 PUFA) biomarkers (including plant derived α linolenic acid and seafood derived eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid) with incident chronic kidney disease (CKD). Design Pooled analysis. Data sources A consortium of 19 studies from 12 countries identified up to May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
(134 reference statements)
0
10
0
Order By: Relevance
“…Fish, recommended by the Food-Based Dietary Guidelines, is a high-protein, high-fat food source ( Cámara et al, 2021 ) Omega-3 polyunsaturated fatty acids (n-3 PUFAs) are found in three main forms: Alpha-linolenic acid, eicosapentaenoic acid, and docosahexaenoic acid ( Shin & Chang, 2023 ). Earlier animal studies suggest that n-3 PUFAs positively impact renal function; however, limited evidence from human studies supports this claim ( Ong et al, 2023 ). n-3 PUFAs are primarily sourced from seafood, such as salmon.…”
Section: Resultsmentioning
confidence: 99%
“…Fish, recommended by the Food-Based Dietary Guidelines, is a high-protein, high-fat food source ( Cámara et al, 2021 ) Omega-3 polyunsaturated fatty acids (n-3 PUFAs) are found in three main forms: Alpha-linolenic acid, eicosapentaenoic acid, and docosahexaenoic acid ( Shin & Chang, 2023 ). Earlier animal studies suggest that n-3 PUFAs positively impact renal function; however, limited evidence from human studies supports this claim ( Ong et al, 2023 ). n-3 PUFAs are primarily sourced from seafood, such as salmon.…”
Section: Resultsmentioning
confidence: 99%
“…Low-fat dairy products, protein from plant-based food (i.e., legumes and cereals) or from selected animal products (i.e., small fish and white meat) can contribute to maintain a healthy lipid profile. Moreover a positive impact on kidney function (8% lower risk) was measured in individuals consuming omega-3 polyunsaturated fatty acids from seafoods ( 10 ). In conclusion the correct lifestyle (food intake and physical activity) can prevent obesity and hypertension in children and adolescents; education needs to start from both parents and children.…”
Section: Nutrition Related Factorsmentioning
confidence: 99%
“…Several studies examining the effect of ω‐3 polyunsaturated fatty acids (ω‐3‐PUFAs) supplementation on human health suggest that they may help reduce several chronic diseases such as diabetes, cardiovascular and inflammatory disorders, hypertension, dyslipidemia, and kidney dysfunction (Arredondo‐Mendoza et al., 2020; Creus et al., 2017; El‐Feky et al., 2022; Y.‐X. Liu et al., 2023; Meyer & De Groot, 2017; Ong et al., 2023; Onneken, 2018; Penson & Banach, 2020; Y. Xiao et al., 2022; X. Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%